Expanding the dimensions of knowledge hiding: testing a moderated mediation model and analyzing the mediating role of psychological distress using PLS-SEM - Jin, Xiu; Jin, Shanyue; Qing, Chenglin (Frontiers in Psychology, 2023)
This study sheds light on the literature on knowledge hiding behavior in organizations and highlights a better and deeper understanding of the reasons for giving rise to knowledge hiding. In recent decades, knowledge hiding has been subjected to numerous studies in systematic literature reviews and organizational management regarding its impact on outcomes such as individual and organizational performance; however, the mechanism by which knowledge hiding is influenced by antecedents and the process of leading knowledge hiding has not been actively verified. In addition, most previous studies have classified knowledge hiding into one-factor or three-factor dimensions: evasive hiding, playing dumb, and rationalized hiding. To address these issues and limitations, this study aimed to broaden the existing literature on the dimensions related to knowledge hiding.Additionally, empirical research was conducted on four new dimensions (playing dumb, evasive hiding, rationalized hiding, and procrastination) of knowledge hiding behavior.Unlike previous research, we provide a research framework for the process of hiding knowledge and verify the significance of the research model. Drawing on the social exchange theory and conservation of resources theory to explored and verified the process of hiding knowledge. Specifically, we argue that knowledge hiding is caused by exploitative leadership, and psychological distress as mediators in the relationship between these two variables. Moreover, the moderating and mediating effects of leader incivility were verified.To empirically test the research model, a survey was conducted with 287 employees from smalland medium-sized enterprises in China. Partial least squares structural equation modelling (PLS-SEM), SPSS PROCESS, and AMOS software were used for statistical analyses. The findings provide evidence that exploitative leadership positively influences both psychological distress and the four dimensions of knowledge hiding. In addition, the mediating effect of psychological distress and moderating effect of leader incivility were verified and shown to be statistically significant.Based on these findings, the theoretical and practical implications, limitations, and directions for future research are discussed. Overall, the most important contributions are expanding the research field, as this is the first empirical study on the four dimensions of knowledge hiding.